2000
DOI: 10.1128/jvi.74.18.8268-8276.2000
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a Minimal Size Requirement for Termination of Vesicular Stomatitis Virus mRNA: Implications for the Mechanism of Transcription

Abstract: The nonsegmented negative-strand RNA (NNS) viruses have a single-stranded RNA genome tightly encapsidated by the viral nucleocapsid protein. The viral polymerase transcribes the genome responding to specific gene-start and gene-end sequences to yield a series of discrete monocistronic mRNAs. These mRNAs are not produced in equimolar amounts; rather, their abundance reflects the position of the gene with respect to the single 3-proximal polymerase entry site. Promoter-proximal genes are transcribed in greater a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
61
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 58 publications
(63 citation statements)
references
References 54 publications
2
61
0
Order By: Relevance
“…Earlier work showed that a polymerase must copy a minimum length of template in order to respond to an authentic gene end sequence (41). This length was Ͼ56 nt, which is reached by the cap-defective mutants despite their defect in the synthesis of full-length N mRNA.…”
Section: Resultsmentioning
confidence: 99%
“…Earlier work showed that a polymerase must copy a minimum length of template in order to respond to an authentic gene end sequence (41). This length was Ͼ56 nt, which is reached by the cap-defective mutants despite their defect in the synthesis of full-length N mRNA.…”
Section: Resultsmentioning
confidence: 99%
“…VSV-eGFP (enhanced green fluorescent protein) and VSV-EBOV (Ebola virus) were previously generated (35,37). All the viruses were propagated on BSRT7 cells in DMEM supplemented with 2% FBS and penicillinstreptomycin/kanamycin.…”
Section: Methodsmentioning
confidence: 99%
“…An infectious cDNA clone of VSV (Whelan et al,'95) engineered to express the marker gene, GFP, VSV-GFP has been previously described (Whelan et al, 2000;Cherry et al, 2005). The coding sequence of GFP, flanked by the essential VSV gene-start and -end sequences, was inserted between the 3′ leader regulatory region and the VSV N gene.…”
Section: Resultsmentioning
confidence: 99%
“…An infectious cDNA clone of the Indiana serotype of VSV (Whelan et al,'95) engineered to express green fluorescent protein (GFP), VSV-GFP (Whelan et al, 2000;Cherry et al, 2005), was propagated in baby hamster kidney (BHK-21) cells (American Type Culture Collection, Manassas, VA) in Dulbecco's Modified Eagle Medium (Invitrogen) supplemented with 10% (v/v) FBS, 2 mM L-alanyl-L-glutamine (Glutamax, Invitrogen), 100 units/ml penicillin, and 100 μg/ml streptomycin. Initial infection was made with a multiplicity of infection of 0.01 in serum-free medium for 1 hr at 37 °C.…”
Section: Propagation Of Vsv-gfpmentioning
confidence: 99%
See 1 more Smart Citation